METODE IJTIHAD IMAM HANAFI DAN IMAM MALIK - Askar Saputra (Jurnal Syariah Hukum Islam, 2018)
This research determined to the pattern of Ijtihad of imam Hanafi and Imam Maliki. The The mindset used by the scholars of the four schools of thought emphasizes the maturity of attitude and tolerance in the face of various problems. The study of Islamic law that they do is always based on the Qur'an and Sunnah. Factor sociology and culture could be impact to how make decision about Islamic law. Based on research, It was found that Imam Hanafi was speaking with sources Al-Quran, As-Sunnah, Al-Ijma`, Al-Qiyas, Al-Istihsaan, Al-'Urf. Then, the source of the law used by Imam Malik looks more than what Imam Hanafi used, it is Al-Quran, As-Sunnah, Al-Ijma`,Al-Qiyas, Al-Istishlaah, Al-Istihsan, Al-'Urf, Khabar Ahad and Qiyas, Qoul Shohabi, Amal Ahli Medina, Sadd Ad-Dzari`ah, Istishaab and. Syar`u Man Qoblanaa